Intimate Partner Violence Among Chinese Transwomen: Associations With Sexual Risk Behaviors and HIV Testing. Issue 5 (15th May 2021) - Wang, Liying; Barile, John P.; Simoni, Jane M.; Harris, Rachel; Yue, Qing; Fu, Jie; Zheng, Huang; Ning, Zhen; Wong, Frank Y.
Abstract : A study of transwomen in Shanghai, China, found that a high prevalence of intimate partner violence among transwomen and those with intimate partner violence experience was less likely to report HIV/sexually transmitted infections testing. Supplemental digital content is available in the text. Abstract : Background: Intimate partner violence (IPV) is an emerging risk factor for HIV infection. Given the high vulnerability of and limited research on transwomen in China, we described IPV, sexual risk behaviors, HIV, and sexually transmitted infection (STIs) testing rates and results, and investigated the pathways that link IPV to HIV infection among this population. Methods: We conducted a cross-sectional survey and collected blood samples for HIV and syphilis testing among transwomen in Shanghai, China (n = 199). With logistic regression, we examined sexual risk behaviors and HIV/STI testing history among participants with and without IPV experience. Results: More than half of the respondents reported IPV (57.3%), and the prevalence of unprotected sex ranged from 51.9% (with sex workers) to 87.8% (oral sex); 85.9% had ever tested for HIV and 49.3% for other STIs. Self-reported positivity results were as follows: HIV (2.3%), herpes simplex virus type 2 (8.3%), gonorrhea (18.8%), and syphilis (17.8%). Laboratory-confirmed positivity values were 5.0% for HIV and 6.5% for syphilis. Respondents with a history of IPV were significantly less likely to report HIV testing in the past 12 months (adjusted odds ratio, 0.20; 95% confidence interval, 0.10–0.38). Conclusions: Transwomen self-reported a high prevalence of IPV, which was related to a lower probability of HIV testing. The prevalence of HIV and other STIs was lower than reported in previous studies of Chinese transwomen, whereas the HIV/STI testing rates were higher. Findings suggest transwomen in China are at risk for IPV and need enhanced HIV prevention services to promote HIV testing in an IPV setting.